Accelerating pH-universal hydrogen-evolving activity of a hierarchical hybrid of cobalt and dinickel phosphides by interfacial chemical bonds. (January 2022) - Liao, Liling; Cheng, Cheng; Zhou, Haiqing; Qi, Ying; Li, Dongyang; Cai, Fengming; Yu, Bo; Long, Run; Yu, Fang
Abstract: A big challenge for hydrogen generation from electrocatalytic water splitting is the development of highly active and stable hydrogen-evolving electrocatalysts from noble-metal-free materials with excellent pH universality, since various water sources such as seawater, industrial wastewater and residential water can be employed as ideal ingredients. However, most of the available inexpensive electrocatalysts cannot exhibit superb catalytic activities in acidic, neutral and alkaline electrolytes with different pH values. Here we report an active and durable hybrid electrocatalyst based on metal phosphides in-situ synthesized on conductive Ni foam, which is demonstrated to exhibit Pt-like activity over a wide pH range. It requires as low as 36, 54 and 57 mV to achieve 10 mA cm −2 in acidic, neutral and basic environments, respectively, outperforming most of the pH-universal hydrogen-evolving electrocatalysts made of earth-abundant and non-noble elements. In particular, this CoP/Ni2 P hybrid exhibits exceptional large-current durability for hydrogen evolution in different pH electrolytes, indicating its potential application for large-scale H2 production. Density functional theory studies confirm that the outstanding catalytic activity of this hybrid is attributed to the strong synergistic effects between the CoP(101) and Ni2 P (001) planes, which lead to low Gibbs free energy for hydrogen adsorption. This work provides a simple and straightforward strategy toward the design and development of inexpensive and efficient all-pH electrocatalysts for hydrogen evolution reaction. Graphical abstract: Image 1 Highlights: A robust and stable pH-universal electrocatalyst is designed by growing cobalt phosphide (CoP) nanowire arrays in direct contact with dinickel phosphide/Ni foam. This catalyst exhibits superb catalytic activities requiring only 36, 54 and 57 mV at 10 mA cm −2 in acidic, neutral and basic solutions, respectively. This hybrid catalyst exhibits promising operational durability at current densities up to 1 A cm −2 with excellent pH compatibility in different media. The outstanding activity of this hybrid is related to strong synergistic effects between CoP(101) and Ni2 P (001) planes, leading to low Gibbs free energy.